Critical disease burdens of Australian adults with cystic fibrosis: Results from an online survey - Ward, Anastasia; Mauleon, Ramil; Arellano, Jacinta; Ooi, Chee Y.; Rosic, Nedeljka (Wiley, 2023)
The objective of this study was to conduct a web‐based questionnaire to investigate self‐reported phenotypes and disease burdens of individuals living in Australia and diagnosed with cystic fibrosis (CF) using a case–control study design.MethodsAn online questionnaire was distributed to individuals with CF and healthy control subjects. Overall health rating, medications, family history, education, clinical indicators of disease, and symptoms, including their severity and frequency, were evaluated.ResultsThere was a total of 119 respondents consisting of 59 people living with CF and 60 controls. The CF cohort had significantly lower tertiary educational levels compared to controls. The analysis specific to the CF cohort depicted a significant correlation between the frequency of hospitalizations and the level of education in the CF cohort. Of the 26 self‐reported symptoms of CF that were analyzed, 14 were significantly higher in the people living with CF. The CF cohort reporting symptoms of chronic pain (25%) described an increase in the burden of disease, depicting a 30% longer mean hospitalization, increased consumption of medications and significant relationships with four other symptoms, including muscle aches, digestive issues, pancreatic insufficiency, and abdominal swelling.ConclusionsThe nationwide survey identified a diverse range of clinical manifestations experienced by the Australian CF population. Chronic pain, linked to aging and the changing landscape of disease, was a significant indicator of the burden of disease. A comprehensive understanding of the phenotypic profiles and symptom variability will contribute to future research and provide insights into the impacts of disease and the burden of therapy, particularly in children, at the start of their health journey.